Individual, Prenatal, Perinatal, and Family Factors for Anxiety Symptoms Among Preschool Children - Ding, Xiuxiu; Wang, Jun; Li, Ning; Su, Wanying; Wang, Hao; Song, Qiuxia; Guo, Xianwei; Liang, Mingming; Qin, Qirong; Sun, Liang; Chen, Mingchun; Sun, Yehuan (Frontiers in Psychiatry, 2021)
Anxiety is one of the most common psychological disorders among children. Few studies have investigated the prevalence and comprehensive factors for anxiety among preschool children in China. This study aimed to assess the prevalence of anxiety and explore influential factors at multiple levels including individual, prenatal and perinatal, and family factors, associated with anxiety symptoms among preschool children. The multisite cross-sectional study was conducted in Anhui Province and included 3636 preschool children aged 3-6 years. Anxiety symptoms of children were assessed using the Chinese version of the Spence Preschool Anxiety Scale. Logistic regression analyses were performed to explore associations between factors at multiple levels and significant anxiety symptoms, and the model was validated internally using 10-fold cross-validation. Among the participates, 9.1% of children had significant anxiety symptoms. Girls reported more significant anxiety symptoms. Children’s poor dietary habits, sleep disturbances, autistic tendencies, and left-behind status; maternal poor prenatal emotional symptoms; and more caregivers’ anxiety symptoms were significantly associated with anxiety symptoms among children. The result of 10-fold cross-validation indicated that the mean area under the curve, sensitivity, specificity, and accuracy was 0.78, 70.45%, 78.18%, and 71.15%, respectively. These factors were slightly different among different subtypes of anxiety symptoms. The results of this study suggested that anxiety symptoms in preschool children were prevalent, particularly in girls. Understanding early-life risk factors for anxiety is crucial, and efficient prevention and intervention strategies should be implemented in early childhood even pregnancy.